Original paperDoes concentration influence viability of the bronchial epithelial cell line chronically exposed to antiasthmatic drugs? - Oleś, Dominika; Szczepankiewicz, Aleksandra; Wołuń-Cholewa, Maria; Butowska, Wanda; Sobkowiak, Paulina; Kycler, Zdzisława; Warchoł, Jerzy; Bręborowicz, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Bronchial epithelial cell lines enable analysis of influence of different factors, such as exposure to inhaled antiasthmatic agents, on their morphology and function in vitro . Aim : To investigate whether chronic exposure to different concentrations of therapeutic agents used in the inhalation therapy of asthma influence bronchial epithelial cells growth and morphology. Material and methods: Bronchial epithelial cell line 16HBE14o- was used. We analyzed changes in viability between cells treated with different drug concentrations: budesonide, fluticasone propionate, salbutamol and ipratropium bromide. Observations were performed every 24 h for 4 days. Cells viability was analyzed by fluorescent staining and XTT assay. Results : An inverse correlation between drug concentration and cells viability was observed. The only exception was ipratropium bromide which was toxic at all studied concentrations. Steroids at the two highest concentrations led to a significant decrease in cells viability with fluticasone propionate being more potent than budesonide. Incubation with salbutamol also demonstrated decreased cells viability at the two highest concentrations. Ipratropium bromide was toxic for the bronchial cells at all concentrations leading to a significant decrease in cells viability. Conclusions : Chronic exposure to the highest concentrations of steroids or β 2 -agonists decreases viability of epithelial cells, whereas ipratropium bromide has the strongest influence on cell viability regardless of its concentration.